Led Zeppelin the biography - Spitz, Bob (Penguin Press, 2021)
"From the author of the definitive New York Times bestselling history of the Beatles comes the authoritative account of the group Jack Black and many others call the greatest rock band of all time, arguably the most successful, and certainly one of the most notorious. Rock stars. Whatever those words mean to you, chances are, they owe a debt to Led Zeppelin. No one before or since has lived the dream quite like Jimmy Page, Robert Plant, John Paul Jones, and John Bonham. In Led Zeppelin, Bob Spitz takes their full measure, for good and sometimes for ill, separating the myth from the reality with the connoisseurship and storytelling flair that are his trademarks. From the opening notes of their first album, the band announced itself as something different, a collision of grand artistic ambition and brute primal force, of delicate English folk music and hard-driving African-American blues.